Der Informationsgehalt von Derivaten für die Geldpolitik: Implizite Volatilitäten und Wahrscheinlichkeiten - Holger Neuhaus (Deutsche Bundesbank, 1995)
There is much discussion about derivatives at central banks. The main focus is on questions about the impact of the growing use of derivative instruments on the stability of the financial markets and the effectiveness ofmonetary policy measures. Irrespective ofthe answers, the information contained in the prices of derivatives can be recovered and used by monetary policy-makers for the monetary policy decision process and operational purposes. Since option prices - unlike, for instance, futures or forward rates - by construction also contain information on the expected price or rate fluctuations of the underlying and in fact also on the probability distributions of future events, the focus of the present study is on options.
Keywords: 330; Zinsderivat; Optionsgeschäft; Börsenkurs; Volatilität; Optionspreistheorie; Wirtschaftsindikator; Zins; Prognose; Deutschland